(untitled) (LACCEI, 2024)
The objective of this research work is to determine the influence of Green Marketing on the brand image of the company AguaFiel Trujillo in the period 2022, since it has been seen that companies have currently chosen to implement Green Marketing strategies and have obtained good results. Definitely, Green Marketing is a strategy that many entrepreneurs have currently put into practice, therefore, most of their products are made of biodegradable materials that contribute to reducing pollution in the environment, creating awareness among consumers in a way who are willing to pay more knowing that they are not only buying but also contributing to an improvement. This research of applied type of non-experimental design with correlational cut had as object of study those people who have consumed the AguaFiel brand, the sample was 165 people. As a technique for data collection, a survey was carried out, with which the result was that there is a significant positive relationship in moderate intensity between the variables of the present study, with an influence of 51.3% of Green Marketing on the brand image, based on to R squared = 0.536 obtained in the coefficient of determination test. As a conclusion, it was obtained that the influence that Green Marketing has on the brand image of the AguaFiel Company in the year 2022 is 51.3% with a significant influence of 118,183, for which it is proposed to improve the presentation and design of the product, highlighting the green label on the package.